Pengaruh Perceived Value of Internship dan Self-Efficacy Terhadap Employability Skills Mahasiswa Universitas Negeri Jakarta - Alifah, Rafha Naisa; Kartikowati , Rr Sri; Maulida, Ervina (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Perceived Value of Internship (PVI) and Self-Efficacy (SE) on the Employability Skills (ES) of students at the Faculty of Economics and Business, Jakarta State University, who have participated in an internship program. The study used a quantitative approach with an explanatory survey method. The sample consisted of 181 students selected using a simple random sampling technique. Data were collected using a 6-point Likert scale questionnaire and analyzed using multiple linear regression. The results showed that PVI and SE had a positive and significant effect on ES, both partially and simultaneously. The coefficient of determination (R²) value of 0.666 indicates that 66.6% of the variation in ES can be explained by PVI and SE. These findings suggest that the improvement of students' employability skills is influenced by the quality of their internship experience and their confidence in their abilities. Therefore, universities need to improve the quality of their internship programs and support the development of students' self-efficacy to enhance graduates' employability.